(untitled) (Euro-Asia Conferences, 2021)
This article discusses the relationship between language and culture in the analysis of linguocultural aspects of phraseology. Phraseologisms are a spiritual treasure that enriches the language and its content, and they are a linguistic and cultural object that unites the culture of the nation.